Duncan Pritchard’s Epistemic Angst - Greco, John (International journal for the study of skepticism, 2018)
Epistemic Angst: Radical Skepticism and the Groundlessness of our Believing. By Duncan Pritchard. Princeton and Oxford: Princeton University Press, 2016. Pp. xv + 239. isbn 978-0-691-16723-7.